Using storytelling to teach vocabulary in language lessons: does it work?. Issue 1 (2nd January 2016) - Kirsch, Claudine
Abstract : It has long been claimed that stories are a powerful tool for language learning. Storytelling is often used as a discrete pedagogical approach in primary modern foreign language (MFL) lessons in England. There has, however, been little investigation into how storytelling might impact on vocabulary learning in the primary classroom. This article focuses on how a London primary teacher used stories in German lessons in a Year 6 class (ages 10–11), and analyses the words and sentences the case-study children remembered over a brief period of time. Data were collected over two terms through observations, interviews and post-tests. The findings illustrate the wide range of teaching strategies that allowed for explicit and incidental learning and encouraged meaningful language use. They also show that children recalled a considerable number of words and sentences.